A General Strategy for Kilogram‐Scale Preparation of Highly Crystal‐line Covalent Triazine Frameworks. Issue 25 (11th April 2022) - Sun, Tian; Liang, Yan; Luo, Wenjia; Zhang, Lei; Cao, Xiaofeng; Xu, Yuxi
Abstract: Scalable and eco‐friendly synthesis of crystalline porous covalent triazine frameworks (CTFs) is essential to realize their broad industrial applications but remains a great challenge, which requires the fundamental understanding of the two‐dimensional polymerization mechanism. Herein, we report a universal polyphosphoric acid (H6 P4 O13 )‐catalyzed nitrile trimerization route to synthesize a series of highly crystalline CTFs with high specific surface areas. This new strategy enables the cost‐effective large‐scale fabrication of crystalline CTFs at kilogram level for the first time. Through density functional theory calculation and detailed controlled experiments, we reveal that the polyphosphate acid show much higher catalytic activity for trimerization reaction than its analogues such as P2 O5 and H3 PO4 . Furthermore, the crystalline CTFs with regular porosity and abundant triazine groups exhibit ultrahigh removal efficiency of micropollutants, indicating its great potential in environment remediation. Abstract : A general polyphosphoric acid (H6 P4 O13 )‐catalyzed strategy is developed to synthesize a series of highly crystalline covalent triazine frameworks (CTFs) with high specific surface areas at the kilogram level for the first time. The polymerization mechanism study reveals a much higher catalytic activity of H6 P4 O13 than its analogues such as P2 O5 and H3 PO4 . Crystalline porous CTFs can be practically used as a highly efficient adsorbent for large‐scale antibiotic removal.